Research About the Policy of Soviet Government Toward Kurdish Mahabad Republic - Nazdar JaIil Mustafa (QALAAI ZANIST JOURNAL, 2022)
The study of the history of Kurdish Mahabad Republic is considered one of the studies and topics which got the interest of writers and rescarchers, particularly the part which is aloowt the saviet Government policy to ward the establishment this fresh Repulic and them its role in ending it (declining). In accordance with its importance, we will shed same light on this important topic of the contemporary history of kurds. The experience of Kurdish Mahabad history is considered one of the most important and unique of the history of kurds. They succeeded in establishing an independent Rebublic in Kurdistan of Iran. But the policy of the colonialism state toward this republic played aralr in declining it, Particulary, the policy of Soviet Union which has an effective impact toward kurds and its question. Thin report consists of three sections. The first one is about the occupation of the Soviet forces of the Kurdistan of Iran and its policy toward kurds unit the establishment of Mahabad Republic, whereas we mentioned in the second section the role of Soviet Union in Establishing the Kurdish Mahabad Repulic which has a great role in letting kurds and the judge Mohammad in announcing the dependence of Mahabad in 1946. The third and the last section tackles the details concerning the Soviet role in declining Mahabad Republic. This section shows the torturing, suffering, practicing pressure on kurds throughout its long history by the colonialists’ states. After Soviets goving a chance to establish this Republic, it withdrew from thin care when it got a treaty from Iranian Government abaut oil. So, the young republic was eliminated.